2009
DOI: 10.2503/jjshs1.78.6
|View full text |Cite
|
Sign up to set email alerts
|

Mutant Resources for the Miniature Tomato (<i>Solanum lycopersicum</i> L.) &lsquo;Micro-Tom&rsquo;

Abstract: Mutant-based studies have contributed to the elucidation of gene functions in plants including tomato. In this review, we introduce some outstanding research performed using spontaneous and artificially induced mutants. Tomato (Solanum lycopersicum L.) is a model species in the solanaceae family and research tools and information necessary to perform functional genomics study are being developed worldwide. Saturation mutagenesis is a powerful strategy that enables exploration of gene function on a genome-wide … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2019
2019

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 62 publications
1
8
0
Order By: Relevance
“…Mutation screens in the other tomato populations show similar frequencies as the one observed in the present study: Saito and co-workers [ 24 ] estimated their mutation frequency to be of 1 mutation event per Mb screened. Moreover in a recent study using direct sequencing with 454 GS FLX Rigola and co-workers [ 38 ] identified 2 mutations in 889 bp of the Sle IF4E gene in 3008 M2 families of the M82 population, resulting in a mutation density of 0.75 mutation per 1000 Kb screened.…”
Section: Resultssupporting
confidence: 83%
See 1 more Smart Citation
“…Mutation screens in the other tomato populations show similar frequencies as the one observed in the present study: Saito and co-workers [ 24 ] estimated their mutation frequency to be of 1 mutation event per Mb screened. Moreover in a recent study using direct sequencing with 454 GS FLX Rigola and co-workers [ 38 ] identified 2 mutations in 889 bp of the Sle IF4E gene in 3008 M2 families of the M82 population, resulting in a mutation density of 0.75 mutation per 1000 Kb screened.…”
Section: Resultssupporting
confidence: 83%
“…One was developed on the M82 line in Israel [ 22 ]. The Micro-Tom [ 23 ] miniature tomato cultivar was also EMS mutagenised, first in the French National Institute of Agricultural Research (INRA) and later in the University of Tsukuba [ 24 ].…”
Section: Introductionmentioning
confidence: 99%
“…Although a melatonin‐rich mutant line of St. John’s wort ( Hypericum perforatum ) has been identified [38], the gene(s) responsible for the trait are unknown because of a lack of genomic resources. However, many tools exist for functional genomics studies in Micro‐Tom, including mutant and full‐length cDNA collections, high‐throughput genetic transformation [39], the TILLING platform and DNA markers [32], and a BAC library (H. Ezura and E. Asamizu, unpublished data). These resources will help define the role of melatonin in plant development.…”
Section: Discussionmentioning
confidence: 99%
“…Leaflets, leaf stems, stems, roots, flowers, fruits, seedlings, and seeds were collected and immediately frozen at )80°C until melatonin extraction. Developing fruits were collected at 10,14,18,22,26,28,30,32, and 34 days after flowering (DAF). Fruits at 10-26 DAF, which were not fully expanded and still green, were defined as Ôimmature greenÕ.…”
Section: Plant Materials and Growth Conditionsmentioning
confidence: 99%
“…Phylogenic analysis of tomato and its inclusion in the Genus Solanum (Asamizu and Ezura, 2009), 2) Mutant resources for tomato and the status of newly developed tools for using the mutant resource (Saito et al, 2009), 3) Application of metabolomics to improve tomato fruit productivity and quality (Iijima and Aoki, 2009), and 4) Web databases for omics data in tomato (Suzuki et al, 2009). I hope the information in this special issue will be useful not only for researchers who are currently working on tomato, but also for young investigators who are planning to jump in the research area of the tomato.…”
mentioning
confidence: 99%